Kyrgyz Republic (Technical Assistance Reports, 2026)
This technical assistance mission assesses options for the improved management of government wages and employment. The key focuses are to: (1) Assess wage levels and dispersion across key public sector occupations, (2) Examine recruitment, retention, and motivation challenges, (3) Identify wage and headcount gaps, (4) Explore international best practices and country cases, (5) Discuss fiscal space and policy options for wage adjustments.